Infeksi virus hepatitis b pada karyawan rumah sakit di yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRAK Hospital personnel, especially those who have direct contact with patients or patience blood, are highly exposed to hepatitis 13 virus. The results of anti-HBs and HBsAg examinations, using the PHA and IIPHA methods, were cross-tabulated by task, gender and length of employment. Among the 843 personnel, consisting of 650 females and 193 males, 23 were positive liBsAg (2.72%) and 111 positive anti-HBs (13.16%). No statistically significant differences in hepatitis serologic marker prevalence were found between the task and gender groups. There was, however, a significant difference between the length of employment groups.